2019
DOI: 10.1002/14651858.cd005612.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin add-on for drug-resistant focal epilepsy

Abstract: Study characteristics This review examined data from 9 trials including a total of 3327 participants. Study participants were assigned using a random method to take pregabalin, placebo, or another antiepileptic drug in addition to their usual antiepileptic drugs. Key results Participants taking pregabalin were more than twice as likely to have their seizure frequency reduced by 50% or more during a 12week treatment period compared to those taking placebo, and were nearly four times more likely to be completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
2
5
0
2
Order By: Relevance
“…The present study revealed no significant reduction in 28‐day GTC seizure frequency with adjunctive pregabalin treatment compared with placebo treatment. Although no significant reduction in GTC seizure frequency or responder status was seen, pregabalin did not increase GTC or myoclonic seizures and demonstrated a safety profile consistent with the known safety profile in patients with other epileptic syndromes, including in adults and children with FOS 17,18,26,33 . The most common AEs reported in adults with FOS include dizziness, somnolence, and weight gain, 17 consistent with the common AEs recorded in this GTC population.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The present study revealed no significant reduction in 28‐day GTC seizure frequency with adjunctive pregabalin treatment compared with placebo treatment. Although no significant reduction in GTC seizure frequency or responder status was seen, pregabalin did not increase GTC or myoclonic seizures and demonstrated a safety profile consistent with the known safety profile in patients with other epileptic syndromes, including in adults and children with FOS 17,18,26,33 . The most common AEs reported in adults with FOS include dizziness, somnolence, and weight gain, 17 consistent with the common AEs recorded in this GTC population.…”
Section: Discussionsupporting
confidence: 72%
“…Although no significant reduction in GTC seizure frequency or responder status was seen, pregabalin did not increase GTC or myoclonic seizures and demonstrated a safety profile consistent with the known safety profile in patients with other epileptic syndromes, including in adults and children with FOS. 17,18,26,33 The most common AEs reported in adults with FOS include dizziness, somnolence, and weight gain, 17 consistent with the common AEs recorded in this GTC population. We observed a gradual decline in GTC seizure frequency in all three treatment arms over the treatment period; however as patients were allowed to continue stable concomitant medications during the treatment phase, these may have influenced these observations.…”
Section: Discussionsupporting
confidence: 53%
“…The evidence for pregabalin use in central neuropathic pain, such as poststroke pain, is limited and a recent meta‐analysis described it as inadequate 18 . Pregabalin is not indicated as monotherapy in epilepsy as the evidence of effect is as an add‐on only 19,20 . As the present study analyses first dispensation of AED (ie, incident treatment), we interpret virtually all pregabalin to be on the indications neuropathic pain or generalized anxiety syndrome 20 .…”
Section: Discussionmentioning
confidence: 81%
“…Despite meta-analyses do not seem to disfavour TGB, the association with cases of status epilepticus [38] made this drug less and less popular. There are three trials comparing pregabalin (PGB) to LTG, LEV and GBP, showing that PGB has higher response rates than LTG (RR 1.47; 95%CI 1.03-2.12) but not higher than LEV or GBP [39].…”
Section: Adjunctive Treatmentmentioning
confidence: 99%